Testing of PEF method to assess the environmental footprint of buildings – results of PEF4Buildings project. (August 2019) - Spirinckx, C; Thuring, M; Damen, L; Allacker, K; Ramon, D; Mirabella, N; Röck, M; Passer, A
Abstract: The aim of the PEF4Buildings project, commissioned by the European Commission, was to assess if the Product Environmental Footprint (PEF) method and related guidance documents developed in the framework of the Environmental Footprint pilot test phase are applicable at the building level. The project has been coordinated by VITO with TU Graz and KU Leuven as research partners. As a first step, two PEF studies on new office buildings were performed. The assessment of two office buildings allows to test the PEF method in different geographical contexts. In a second step, a possible approach to benchmark office buildings and to define classes of performance is developed. The approach is developed based on the findings of the PEF study on two new office buildings, the PEF guidance and dedicated desk research. It covers issues like how to define the reference building, how to define system boundaries, how many reference buildings should be defined and how to handle this range of different options. A third step of this study was devoted to the assessment at the building level and on how to link the assessment of the environmental performance of construction products to the assessment of a building by using the PEF method.